2018
DOI: 10.1016/j.ygcen.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the corticosteroid signalling system in rainbow trout HPI axis during confinement stress

Abstract: This study aims to shed light on corticosteroid regulation of stress in teleost fish with focus on the corticosteroid signalling system. The role of the mineralocorticoid-like hormone 11-deoxycorticosterone (DOC) in fish is still enigmatic, as is the function of the mineralocorticoid receptor, MR. Low plasma DOC levels and ubiquitous tissue distribution of MR question the physiological relevance of the mineralocorticoid-axis. Furthermore, the particular purpose of each of the three corticosteroid receptors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 55 publications
2
21
1
Order By: Relevance
“…Fish subjected to chronic stress showed lower GR levels in the brain (Piato et al, ). Further, changes in rainbow trout GR expression levels in the HPI axis were found after 7 days of confinement (Kiilerich et al, ). As cortisol exerts different effects on various organ systems, it is likely that the functional targets of GR were different in each tissue (Le et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish subjected to chronic stress showed lower GR levels in the brain (Piato et al, ). Further, changes in rainbow trout GR expression levels in the HPI axis were found after 7 days of confinement (Kiilerich et al, ). As cortisol exerts different effects on various organ systems, it is likely that the functional targets of GR were different in each tissue (Le et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As cortisol exerts different effects on various organ systems, it is likely that the functional targets of GR were different in each tissue (Le et al, 2005). The cortisol plasma levels increased after 7 and 14 days of chronic confinement in sea bream (Sparus aurata; Barton, Ribas, Acerete, & Tort, 2005) and rainbow trout (Kiilerich et al, 2018), respectively, but they were recovered in longer confinement experiments (~200 days) in wedge sole (Dicologoglossa cuneate; Herrera, Ruiz-Jarabo, Vargas-Chacoff, de la Roca, & Mancera, 2015). In a similar manner, no difference in cortisol levels was found in juvenile zebrafish subjected to HD during 45 days (Ribas et al, 2017a) but, when sexually mature, GR was downregulated in the gonads at the highest densities, especially in females.…”
Section: Discussionmentioning
confidence: 99%
“…Eissa and Huang (33) have revised thoroughly all genes involved in the fish stress response depending on stressor type, and stated that the use of genomic tools to study the candidate genes associated with stress responses are often unique signatures or imprints of specific stressors and could determine early signs of stressors. Having this in mind, Kiilerich et al (34) have recently studied the expression of glucocorticoid and mineralocorticoid receptors (i.e., GR1, GR2, and MR) at different levels, concluding that the control and release of cortisol after stress is regulated through a negative cortisol feedback occurring at pituitary level; to the date, it was thought that this feedback occurred at every level of the HPI axis. Other authors have concluded that cortisol regulation is also dependent on circulating glucose concentration under acute stress, reporting a stimulatory effect of increasing glucose levels on the cortisol release (35).…”
Section: The Endocrine Stress Response In Fishmentioning
confidence: 99%
“…The brain, kidney, and spleen were collected for RNA-Seq. Previous studies in trout revealed important genes involved in regulating stress responses and immune functions (35)(36)(37)(38)(39)(40); therefore, we targeted these candidate genes (Figure 1). Our studies showed that complement-and TNF-associated immune defenses were specifically activated in AT.…”
Section: Introductionmentioning
confidence: 99%